Psychological problems associated with diagnosis and treatment of lymphomas. I: Retrospective study. Issue 6604 (17th October 1987) - Devlen, J; Maguire, P; Phillips, P; Crowther, D; Chambers, H
Abstract : Patients treated for Hodgkin's disease and non-Hodgkin's lymphoma have a better prognosis than other patients with cancer so may have a lower prevalence of psychological and social morbidity. Trained interviewers used standardised methods to assess 90 patients at a mean of 32 months after the diagnosis of Hodgkin's disease or non-Hodgkin's lymphoma. Chemotherapy and radiotherapy had commonly caused adverse effects including hair loss, vomiting, nausea, and loss of appetite. Although most patients were free of disease and not receiving treatment at follow up, some still suffered from a lack of energy (31 patients), loss of libido (19), irritability (22), and tiredness (19); 30 patients complained of continued impairment of thinking or disturbance of short term memory. After diagnosis 21 patients had suffered from an anxiety state or depressive illness, or both, while 27 had experienced borderline anxiety or depression, or both. Mood disturbance was positively correlated with adverse effects of treatment, particularly those affecting the gastrointestinal tract. Social adjustment was less affected, but failure to return to work, or a long delay in returning to work, and a persistent lack of interest in leisure activities gave cause for concern. These findings of substantial psychiatric and social morbidity in patients with Hodgkin's disease and non-Hodgkin's lymphoma prompted a prospective study of these patients to determine their nature and duration.